2009
DOI: 10.1096/fj.08-128140
|View full text |Cite
|
Sign up to set email alerts
|

Raft component GD3 associates with tubulin following CD95/Fas ligation

Abstract: In a previous investigation, we demonstrated that after CD95/Fas triggering, raft-associated GD3 ganglioside, normally localized at the plasma membrane of T cells, can be detected in mitochondria, where they contribute to apoptogenic events. Here, we show the association of the glycosphingolipid GD3 with microtubular cytoskeleton at very early time points following Fas ligation. This was assessed by different methodological approaches, including fluorescence resonance energy transfer, immunoelectron microscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 48 publications
1
35
0
Order By: Relevance
“…Finally, a recent work also suggested that sphingolipids could act as regulators of the crosstalk between apoptosis and autophagy. 33 In the present work, in agreement with these observations, [15][16][17][18] and with those underlying the presence of GD3 not only on the plasma membrane, but also in the cell cytoplasm, 34,35 including the ER-mitochondria associated membranes, 36 we found that the inhibitor of ceramide synthase FB1 significantly prevented autophagy induced either by amino acid starvation or by tunicamycin. Furthermore, we point out a specific role for ganglioside GD3, since we found that the knocking down of GD3 synthase significantly hindered autophagy.…”
Section: Figure 7 Gd3 Associates With Lc3 and Lamp1 Coimmunoprecipisupporting
confidence: 92%
“…Finally, a recent work also suggested that sphingolipids could act as regulators of the crosstalk between apoptosis and autophagy. 33 In the present work, in agreement with these observations, [15][16][17][18] and with those underlying the presence of GD3 not only on the plasma membrane, but also in the cell cytoplasm, 34,35 including the ER-mitochondria associated membranes, 36 we found that the inhibitor of ceramide synthase FB1 significantly prevented autophagy induced either by amino acid starvation or by tunicamycin. Furthermore, we point out a specific role for ganglioside GD3, since we found that the knocking down of GD3 synthase significantly hindered autophagy.…”
Section: Figure 7 Gd3 Associates With Lc3 and Lamp1 Coimmunoprecipisupporting
confidence: 92%
“…However, the role of lipid rafts in death execution seems to be not merely limited to the plasma membrane, as a role for microdomains has also been observed in the propagation of death stimuli. After the pioneering studies by the group of De Maria 21,22 suggesting an intracellular trafficking of glycosphingolipids, we have shown that (i) the cytoplasmic trafficking of ganglioside GD3, considered as a paradigmatic component of glycosphingolipid microdomains, could occur through its association with cytoskeletal components 28 and (ii) mitochondrial fission-associated proteins are recruited to 'raft-like' lipid microdomains under proapoptotic stimulation. 20 Hence, the data presented here seem to add a novel role for these lipid microdomains, which could contribute to mitochondria remodeling that precedes apoptosis execution.…”
Section: Discussionmentioning
confidence: 99%
“…We applied fluorescence resonance energy transfer (FRET) analysis by flow cytometry to study the colocalization of GHCer and TRAX (17). Briefly, cells were incubated with various amount of GHCer for 5 minutes at 37 C then fixed and permeabilized, washed twice in cold PBS, and then labeled with antibodies tagged with donor (PE) or acceptor (Cy5) dyes.…”
Section: Fluorescence Resonance Energy Transfermentioning
confidence: 99%